Plasma amino acid profiles in dogs with inflammatory bowel disease - Tamura, Yu (J Vet Intern Med, 2019)
BACKGROUND: Lymphocytic‐plasmacytic enteritis is the common form of idiopathic inflammatory bowel disease (IBD) in dogs. In human IBD, disturbances of amino acid metabolism have been demonstrated to be involved in the pathophysiology of IBD. Therefore, plasma amino acid profile might represent a novel marker of human IBD. OBJECTIVES: To determine the plasma amino acid profiles of dogs with IBD and its usefulness as a novel marker of IBD in dogs. ANIMALS: Fasting blood plasma was obtained from 10 dogs with IBD and 12 healthy dogs. METHODS: All IBD dogs were prospectively included in this study, and heparinized blood samples were collected. The plasma concentrations of 21 amino acids were determined using the ninhydrin method. The relationships among the plasma amino acid concentrations and plasma C‐reactive protein (CRP) concentration, canine chronic enteropathy clinical activity index (CCECAI), and overall World Small Animal Veterinary Association (WSAVA) score were investigated. RESULTS: Median concentration (nmol/mL) of methionine [46.2; range, 30.0‐59.3], proline [119.4; range, 76.7‐189.2], serine [115.1; range, 61.4‐155.9], and tryptophan [17.4; range, 11.9‐56.3]) were significantly lower than in control dogs [62.6; range, 51.0‐83.6, 199.1; range, 132.5‐376.7, 164.3; range, 124.7‐222.9, and 68.3; range, 35.7‐94.8, respectively]. A negative correlation was identified between the plasma serine concentration and CCECAI (r (s) = −.67, P = .03), but there were no correlations between plasma amino acid concentrations and CRP concentration or overall WSAVA score. CONCLUSIONS AND CLINICAL IMPORTANCE: Plasma serine concentration might represent a novel maker of IBD in dogs.